2019
DOI: 10.1111/hdi.12769
|View full text |Cite
|
Sign up to set email alerts
|

Daily dietary phosphorus intake variability and hemodialysis patient adherence to phosphate binder therapy

Abstract: Introduction: Phosphate balance could be reached only by an optimized combination of dietary restriction and the careful use of phosphate binders for patients receiving standard hemodialysis treatment. Little is known about individual variability of phosphorus intake and phosphate binder use in hemodialysis patients. The purposes of this study were to quantify phosphorus intake and to describe individual phosphate‐binder use in hemodialysis patients. Methods: This was a cross‐sectional study. The dietary phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Lack of energy and protein intake is a common nutritional problem in these patients. Other studies carried out in Iran [ 32 ] and other countries [ 33 34 ] have shown similar results. It is important to consider that inadequate energy and protein intake in hemodialysis patients worsens malnutrition and increases the risk of mortality [ 34 35 ].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Lack of energy and protein intake is a common nutritional problem in these patients. Other studies carried out in Iran [ 32 ] and other countries [ 33 34 ] have shown similar results. It is important to consider that inadequate energy and protein intake in hemodialysis patients worsens malnutrition and increases the risk of mortality [ 34 35 ].…”
Section: Discussionsupporting
confidence: 79%
“…Other studies carried out in Iran [ 32 ] and other countries [ 33 34 ] have shown similar results. It is important to consider that inadequate energy and protein intake in hemodialysis patients worsens malnutrition and increases the risk of mortality [ 34 35 ]. The most important reason for lack of energy and protein intake in these patients is anorexia, which is the result of different factors, such as inflammation, the accumulation of toxic products, changes in hormones levels (ghrelin and leptin), neural mediators affecting appetite and underlying diseases like infection, and mental disorders.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We used a 3-day food diary to assess sodium intake, a method that may imply inherent errors of dietary assessment and can be the cause of under-and over-reporting. Nevertheless, there is large recent evidence that the 3-day diet diary is a simple, useful, and effective method to measure the intake of macro-and micro-nutrients in patients on chronic hemodialysis [43][44][45][46][47]. The strength is that we included patients of different towns of Italy and consequently the data can be considered representative of the Italian population of patients on chronic hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…This figure includes chronic hemodialysis patients [ 1 ]. Recent studies of medication compliance in hemodialysis patients have mainly assessed the relationship between patients’ preferences, such as dietary intake, and chelating agents [ 9 , 10 ]. Our study analyzed clinical data related to hemodialysis patients, discussed the factors influencing patient medication compliance, and established a nomogram model to predict poor medication compliance in patients undergoing hemodialysis; this nomogram provides a simple and effective tool for identifying high-risk hemodialysis patients with poor medication compliance.…”
Section: Introductionmentioning
confidence: 99%